LEGAL REGIME OF LAND IN THE MINING AREAS ОF MEDIEVAL SERBIA - Andreja B., (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The aim of the research is to cast light on the legal regime of the mining area land in medieval Serbia and to answer to what extent Saxon customary mining law was accepted in this aspect and what the ratio legis of article 123 of Dušan’s Code was?            It seems likely that until the enactment of Dušan’s Code it was possible to occupy land cleared for mining purposes and to acquire property of the mining area, which was previously res nullius. However, Dušan’s Code changed this rule proscribing only the possibility of acquiring the time limited mining concession, which was motived by possible permanent monopolization of the land in the mining areas. At the same time, the Code proclaimed the right of ore search and exploration on the feudal lords’ land. Similarities to the older Hungarian and Czech law indicates legal transplantation.            The mining concession was regulated in Despot Stefan’s Mining Code for Novo Brdo, which proscribed detailed rules for losing the concession in the case of neglecting the mining activity. Based on similarities one can assume that these rules were mostly the reception of the Saxon customary mining law, also written in late medieval mining laws of Hungary and Czechia. However, the small differences may show that after one and a half century the Serbian mining community introduced its own unique rules.             Research is based on linguistic, systematic and historical analysis of the sources as well as the regressive analysis and comparative method.
Keywords: mining law, Dušan’s Code, Mining Code of Despot Stefan, mining concession, occupation of land